2015
DOI: 10.1371/journal.pone.0122913
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral and Thermal Imaging of Oilseed Rape (Brassica napus) Response to Fungal Species of the Genus Alternaria

Abstract: In this paper, thermal (8-13 µm) and hyperspectral imaging in visible and near infrared (VNIR) and short wavelength infrared (SWIR) ranges were used to elaborate a method of early detection of biotic stresses caused by fungal species belonging to the genus Alternaria that were host (Alternaria alternata, Alternaria brassicae, and Alternaria brassicicola) and non-host (Alternaria dauci) pathogens to oilseed rape (Brassica napus L.). The measurements of disease severity for chosen dates after inoculation were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 44 publications
2
55
0
2
Order By: Relevance
“…A relatively small number of works have addressed the study of biotic stress, most of them focused on fungal infections. For example, Baranowski et al (2015) reported the analysis of Alternaria infections in oilseed rape; Calderón et al (2013, 2015) analyzed olive trees infected by Verticillium dahliae ; the infection of almond trees with red leaf blotch was studied by López-López et al (2016); and powdery mildew on tomato plants was investigated by Raza et al (2015). However, other techniques on their own, or combined, could also be of great help in precision agriculture and plant phenotyping, as reviewed by Tremblay et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…A relatively small number of works have addressed the study of biotic stress, most of them focused on fungal infections. For example, Baranowski et al (2015) reported the analysis of Alternaria infections in oilseed rape; Calderón et al (2013, 2015) analyzed olive trees infected by Verticillium dahliae ; the infection of almond trees with red leaf blotch was studied by López-López et al (2016); and powdery mildew on tomato plants was investigated by Raza et al (2015). However, other techniques on their own, or combined, could also be of great help in precision agriculture and plant phenotyping, as reviewed by Tremblay et al (2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among all the imaging techniques employed in this study, the results obtained by thermography revealed significant changes in infected leaves. Differences in temperature, which depended on the Alternaria species, were observed in various stages of the infection [96]. Hellebrand et al [97] studied the possibility of detecting wheat plants infected by powdery mildew (Blumeria graminis) using thermal and NIR imaging under laboratory and field conditions.…”
Section: Thermal Imaging To Monitor Plants Infected With Fungimentioning
confidence: 99%
“…Sacc., and A. brassicicola (Schwein.) Wiltshire infected rapeseed kernels in the NIR region of 1000-2500 nm (Baranowski et al, 2015). The classification models differentiated healthy samples from fungal infected samples with classification accuracy more than 80% at early stage (2 days) and more than 90 at later stages of infection (Baranowski et al,2015).…”
Section: Push-broom Systemmentioning
confidence: 99%